Methane emission in breeding and finishing of bulls with different levels of technology - Lazari, Tatiane Aparecida; Cavali, Jucilene; Porto, Marlos Oliveira; Ferreira, Elvino; Codognoto, Luciane Cunha [UNESP] (Centro Universitario de Maringa, 2019)
Production performance and methane production in two breeding and finishing systems in the state of Rondônia, Brazil, are evaluated. Study comprised totally randomized design, with two treatments, with 128 non-castrated heifers, mean initial weight 281.906 ± 1.69 kg. Production systems were classified by technology level employed, with supplementary pasture and finishing in confinement (SPC) as the highest technology-based production system, and breeding and finishing with supplementary pasture (SP), as average technology level. SP system had the greatest pasturing pressure on breeding, lowest availability of DM (t/ha) and highest stocking rate. Breeding period within the most technical system was reduced to 61 days, with a 41.42% decrease in CH4 per kg of body weight. Finishing cycle was concluded in 94 days prior to the SPC system, with a decrease of 57.20% CH4 emission per kg of body weight gain. Results show that the technology level applied to animal production affects performance. In CH4 evaluation of weight gain, it has the lowest impact on the environment by gas emission, decrease in the animal production cycle and faster financial returns.
Emissão de metano na recria e terminação de bovinos sob diferentes níveis de tecnologia
Keywords: Beef cattle; Confinement; Supplementary pasture; Technical systems